What ideas have you had so far?
I have the following function:
I need to know the derivative of y regarding x.Code:h = k1 - k2 a = (k1 - x) / h b = (x - k2) / h y = a * k3 + b * k4 + ((a^3 - a) * k5 + (b^3 - b) * k6) * (h^2) / 6
Can someone help me out?
Sorry to bother.
I went with my method and it was a mess...
The substitutiom gave:
and I obtained the derivative:Code:y = ((k1-x)/h)*k3+((x-k2)/h)*k4+((((k1-x)/h)^3-((k1-x)/h))*k5+(((x-k2)/h)^3-((x-k2)/h))*k6)*(h^2)/6
Is this right? I'm not sure...Code:y' = ((3*k6-3*k5)*x^2+(6*k1*k5-6*k2*k6)*x+(3*k2^2-h^2)*k6+(h^2-3*k1^2)*k5+6*k4-6*k3)/(6*h)